Platelet-rich plasma, a biomaterial, for the treatment of anterior talofibular ligament in lateral ankle sprain - Zhang, Jieyuan; Wang, Cheng; Li, Xueqian; Fu, Shaoling; Gu, Wenqi; Shi, Zhongmin (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Because of the rising prevalence of anterior talofibular ligament (ATFL) damage, there is a considerable interest in developing innovative techniques to improve the biological healing response of ATFL. Platelet-rich plasma (PRP) includes several growth factors linked to a favorable healing response, however none of the studies involved both quality evaluation and clinical results to evaluate this treatment. Purpose：To determine the clinical results of PRP injections into the ATFL in lateral ankle sprain (LAS) patients, as well as the quality of the ATFL based on radiographic outcomes. Methods: Patients with clinically confirmed grade II LAS for the first time (n=83) were examined. The clinical outcomes of three types of injection methods were evaluated: none, once within 48 hours after the sprain, and once more 4 weeks later after first injection. PRP was injected into the tear site of the ATFL using ultrasound guidance, and all ankles were immobilized for 2 weeks. The American Orthopedic Foot and Ankle Score (AOFAS) ankle-hindfoot scale and the Visual Analogue Scale (VAS) were used to assess the results at 2, 6, 8, 24, and 48 weeks of follow-up. The signal/noise ratio (SNR) value of Magnetic Resonance Imaging (MRI)-based ATFL signal intensity can disclose ATFL quality. The ATFL SNR results were then assessed 8, 24 and 48 weeks following the first injection to compare ATFL quality. Results：The PRP injection groups outperformed the control group in terms of clinical outcomes, and the two injections group outperformed other groups in terms of pain reduction and functional outcome at 8 weeks. The clinical results of all groups were comparable at 6 and 12 months follow-up. ATFL SNR findings improved significantly across all groups over time. At the same follow-up time, the PRP injection groups outperformed the control group, and the best SNR result showed in the two injections group at the final follow-up. Conclusion: PRP injection helped relieve early symptoms of LAS, although all patients saw a similar development after 6 months. The two PRP injections group produced considerably better clinical results and quality of the ATFL in short-term follow-up.